2013
DOI: 10.1007/s10815-013-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Polycystic Ovary Syndrome: AMH in combination with clinical symptoms

Abstract: Purpose We assessed the utility of using anti-Müllerian hormone (AMH) and clinical features of polycystic ovary syndrome (PCOS), polycystic ovarian morphology (PCOM), oligo/amenorrhea (OA), and hyperandrogenism (HA) for diagnosing PCOS, and compared their diagnostic accuracy with those of classical diagnostic systems. Methods A total of 606 females were admitted to a university hospital with menstrual irregularities or symptoms of hyperandrogenism were enrolled in this cross-sectional study. Fasting blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 42 publications
5
45
2
1
Order By: Relevance
“…(3.8 ng/mL) and Wiweko and cols. (4.45 ng/mL) (4,5). In contrast with results published by Kriseman and cols.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…(3.8 ng/mL) and Wiweko and cols. (4.45 ng/mL) (4,5). In contrast with results published by Kriseman and cols.…”
Section: Discussioncontrasting
confidence: 87%
“…Accordingly, several threshold AMH values for PCOS (based on measurements among varied age and ethnic groups) have been proposed. Of note, serum AMH has been considered as a substitute for antral follicle count as articulated by the Rotterdam diagnostic criteria for PCOS (4)(5)(6)(7)(8)(9)(10)(11)(12) although this has not been widely used perhaps due to the lack of a universally standardized AMH serum assay (13).…”
mentioning
confidence: 99%
“…[52]. Additionally, it has been shown that for the diagnosis of PCOS the combination of OM and/or HA with AMH shows 83% sensitivity and 100% specificity according to the Rotterdam criteria [53]. Due to the fact that published studies use different assays, the values of serum AMH obtained in one assay may not be directly translated to the other.…”
Section: Amh In Pcos Diagnosismentioning
confidence: 99%
“…uważają, że przy stężeniu AMH w surowicy krwi > 35 pmol/l lub liczbie pęcherzyków jajnika przekraczającej 19, częstość występowania PCOS była niższa odpowiednio 8,5% i 6,3% w porównaniu z częstością 16,6% przy kryteriach rotterdamskich [52]. Warto zwrócić uwagę, że współwystępowanie OM i/lub HA z podwyższonym stężeniem AMH pozwala na diagnozę PCOS z czułością 83% i specyficznością 100%, według kryteriów rotterdamskich [53]. Do oznaczenia stężenia AMH w surowicy wykorzystywane były różne metody, co sprawia, że uzyskane wyniki nie zawsze mogą być ze sobą porównywane.…”
Section: Amh W Diagnostyce Pcosunclassified
“…Numerous studies demonstrate that PCOS is significantly associated with elevated serum AMH both with the NIH criteria [43 ▪ ,44 ▪ ] and with the Rotterdam criteria [44 ▪ ,45 ▪▪ ,46 ▪▪ ,4749]. One study demonstrated that in women presenting for fertility evaluation with serum AMH elevated, high, and very high, the frequency of PCOS diagnosis was 51.6% ( n  = 84), 97% ( n  = 30), and 100% ( n  = 20), respectively [50 ▪ ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%